Secondary Reserves Determination Based on cps1 and cps2 Compliant Agc Operation - Chavez-Orostica, H; Avila-Araya, T (Institute of Electrical and Electronics Engineers Inc., 2016)
The global initiatives to achieve cleaner ways to generate electricity have motivated non-dispatchable generation to play a major role in the operation of electric power systems. However, this kind of generation along with its variability have increased the need for better control systems to achieve a constant balance between generation and consumption, in order to maintain frequency in their scheduled values. This work presents an AGC model for multiple balancing authorities with high renewable penetration that complies with NERC control performance standards, ensuring secondary control adequacy. An analysis of the reserves required to achieve this operation is presented, obtaining that the joint coordination of the control system of the two control areas decreases the amount of secondary reserves needed to comply with CPS1 and CPS2. © 2016 IEEE.